2015
DOI: 10.1080/09168451.2015.1025034
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of appetite-mediated gene expression in daidzein-fed female rats in the meal-feeding method

Abstract: We previously found that daidzein decreased food intake in female rats. The present study aimed to elucidate the relationship between dynamics of appetite-mediated neuropeptides and the anorectic effect of daidzein. We examined appetite-mediated gene expression in the hypothalamus and small intestine during the 3 meals per day feeding method. Daidzein had an anorectic effect specifically at the second feeding. Neuropeptide-Y (NPY) and galanin mRNA levels in the hypothalamus were significantly higher after feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…Rachoń et al reported that a 400 mg/kg diet of dietary equol decreases food intake and weight gain (13). Dietary daidzein increases serum concentration of S-equol to far higher levels than that of daidzein in female rats in our previous studies (6,9). S-equol may be responsible for decreases in food intake and serum cholesterol concentration in FSBE-and daidzein-fed female rats.…”
Section: Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…Rachoń et al reported that a 400 mg/kg diet of dietary equol decreases food intake and weight gain (13). Dietary daidzein increases serum concentration of S-equol to far higher levels than that of daidzein in female rats in our previous studies (6,9). S-equol may be responsible for decreases in food intake and serum cholesterol concentration in FSBE-and daidzein-fed female rats.…”
Section: Methodsmentioning
confidence: 72%
“…The anesthetics were administered to rats by intraperitoneal injection. At day 7 (Experiment 1), and days 1, 2, 3, and 5 (Experiment 2) after dietary supplementation with daidzein or S-equol, mid-line laparotomy was performed on the rats and the bile duct was then cannulated with a PE-10 polyethylene tube has the anorectic effect, and changes gene expression of appetite-mediated neuropeptides in hypothalamus, an important appetite-control center that integrates peripheral hormone signals and interacts with other brain region (2,6). These results indicate that daidzein is a potential candidate to treat obesity due to their ability to regulate food intake and energy homeostasis.…”
Section: Methodsmentioning
confidence: 99%
“…32) Furthermore, serum equol concentration was more than threefold higher than that of daidzein in non-Ovx rats fed a diet containing 150 mg/kg daidzein. 33) Unpublished results of experiments on Ovx and non-Ovx rats showed that the serum equol concentration was more than 2000 nmol/L in rats fed a diet containing daidzein, regardless of whether the rats had undergone ovariectomy. Thus, the stronger estrogenic and antioxidative activities and higher concentrations could be responsible for the physiological effects of equol compared to genistein in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary daidzein-induced anorectic effect was observed mainly during the second meal, but rarely during the first and third meals [ 48 ]. Interestingly, our findings suggested that daidzein attenuates the postprandial increase in mRNA expression of Npy and Gal , and increased Crh mRNA expression in the hypothalamus ( Figure 3 B–D), concomitantly with the reduction in food intake [ 48 ]. NPY induces potent hyperphagia and obesity [ 49 , 50 ].…”
Section: Daidzein Alters Gene Expression Of Hypothalamic Appetite-rel...mentioning
confidence: 99%
“…Our results suggested that Gal mRNA expression is caused by dietary daidzein-induced increase in Npy mRNA expression. Dietary daidzein significantly increased Cck mRNA expression in the upper small intestine before and after the second meal ( Figure 3 E) [ 48 ]. However, as described above, we have demonstrated that CCK signaling is not essential for the anorectic effects of daidzein [ 44 ].…”
Section: Daidzein Alters Gene Expression Of Hypothalamic Appetite-rel...mentioning
confidence: 99%